2010
DOI: 10.4049/jimmunol.1000450
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of IL-25 in Nematode Infection-Induced Alterations in Intestinal Function

Abstract: IL-25 (IL-17E) is a member of the IL-17 cytokine family. IL-25–deficient mice exhibit impaired Th2 immunity against nematode infection, implicating IL-25 as a key component in mucosal immunity. The sources of IL-25 and mechanisms responsible for the induction of Th2 immunity by IL-25 in the gastrointestinal tract remain poorly understood. There is also little information on the regulation of IL-25 during inflammation or its role in gut function. In the current study, we investigated the regulation of IL-25 dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 34 publications
8
111
1
Order By: Relevance
“…Unlike those of IL-17RC-deficient patients, PBMCs from ACT1-deficient and IL-17RA-deficient patients do not respond to IL-17E/IL-25 (10,11). The role of human IL-17E/IL-25 is unknown, in the absence of known patients bearing specific mutations, but its mouse counterpart is known to promote "Th2"-mediated responses (89,90) and to be involved in immunity to parasitic infections (91)(92)(93). We were unable to detect cellular responses to IL-17B, -17D, and even -17C (83) in control fibroblasts, keratinocytes, or leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike those of IL-17RC-deficient patients, PBMCs from ACT1-deficient and IL-17RA-deficient patients do not respond to IL-17E/IL-25 (10,11). The role of human IL-17E/IL-25 is unknown, in the absence of known patients bearing specific mutations, but its mouse counterpart is known to promote "Th2"-mediated responses (89,90) and to be involved in immunity to parasitic infections (91)(92)(93). We were unable to detect cellular responses to IL-17B, -17D, and even -17C (83) in control fibroblasts, keratinocytes, or leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…191 Intestinal peristalsis is mediated by contraction of smooth muscle cells, and is induced by both IL-9 (ref. 102), IL-4 and IL-13, 27,73,192 and seems to be controlled mainly by T cells. Thus, the responsiveness of smooth muscle cells to neurotransmitters that control contraction via muscarinic receptors are important for N. brasiliensis expulsion.…”
Section: Expulsionmentioning
confidence: 99%
“…[15][16][17]25,[34][35][36][37][38] Epithelium-derived IL-25 and IL-33, in particular, are important for driving IL-5 and IL-13 production from ILC2, the latter of which induces a number of responses, including goblet and tuft cell expansion, resulting in a strong positive feedback loop with increased production of IL-25 by epithelial cells. [15][16][17]31,[34][35][36][37] As a consequence, mice lacking IL-25 have less efficient expulsion of T. muris, 26 T. spiralis, 39 N. brasiliensis, 25,27,40 and H. polygyrus 28 worms. Furthermore, exogenous administration of IL-25 fails to restore expulsion in il13 À / À mice, 25,27 whereas the reverse is true, 15,17 illustrating that IL-25 acts upstream of IL-13 rather than directly on expulsion.…”
Section: Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that epithelial-derived IL-17E was critical for Nippostrongylus brasiliensis expulsion from the intestine. 139 Although many ILC2s (that is, MPP type2 cells, nuocytes and Ih2 cells) can promote type 2 immunity in response to IL-17E, the precise roles of IL-17E and these ILC2s in worm expulsion need to be determined in the future. 9 Exogenous delivery of IL-17E also protects mice from Trichuris muris infection, whereas IL-17E deficiency in mice leads to impaired worm clearance.…”
Section: Il-17dmentioning
confidence: 99%